Study of Glucose-6-Phosphate Dehydrogenase Deficiency: 5 Years Retrospective Egyptian Study - Hagag, Adel A.; Badraia, Ibrahim M.; Elfarargy, Mohamed S.; Abd Elmageed, Mohamed M.; Abo-Ali, Ehab A. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme deficiency worldwide that causes a spectrum of diseases including neonatal hyperbilirubinemia, acute and chronic hemolysis after exposure to oxidative stress. Aim of the Work: This five years retrospective study was carried out to study the demographic, clinical and laboratory data of 1000 patients with G6PD deficiency anemia registered in Hematology Unit, Pediatric Department, Tanta University Hospital. Patients and methods: Data were collected from patient's files, from November 2011 to November 2016, using the pre-designed questionnaires to obtain the complete history, clinical presentation and laboratory investigations including the complete blood count, red blood cells morphology, liver and renal functions and quantitative assay of G6PD enzyme activity by spectrophotometric method. Results: Males were more commonly affected than females (932 males versus 68 females). The highest prevalence of hemolytic crisis in G6PD deficiency patients was found within the age group of 1-3 years (920 patients; 92%) with mean age of the first presentation of 22.8±15.54 months. Patients presented mainly with pallor (1000 patients; 100%), dark red urine (896 patients; 89.6%) and jaundice (878 patients; 87.8%) after 24-72 hours of exposure to the precipitating factors (mean: 36±17.73 hours). Diets were the most common precipitating factor of hemolysis in patients with G6PD deficiency (834 patients; 83.4% of studied cases) especially fava beans (326 patients; 32.6%) and falafel (194 patients; 19.4%) which were the most common precipitating food products causing hemolysis followed by chick pea (108 patients; 10.8%), broad bean (76 patients; 7.6%), green pea (44 patients; 4.4%), pea nuts (38 patients; 3.8%), lentil (28 patients; 2.8%), and lastly black eyed peas (20 patients; 2 %). Infections were the 2nd most common cause of hemolysis (124 patients; 12.4%) including pneumonia (34 patients; 3.4%), tonsillitis (32 patients; 3.2%), typhoid fever (28 patients; 2.8%), hepatitis A (18 patients; 1.8%) and urinary tract infection (12 patients; 1.2%). Drugs were the least common cause of hemolysis (42 patients; 4.2%) including diclofenac sodium (24 patients; 2.4%), ibuprofen (8 patients; 0.8%), acetylsalicylic acid (4 patients; 0.4%), co-trimoxazole (4 patients; 0.4%) and nitrofurantion (2 patients; 0.2%). There was normocytic normochromic anemia with reticulocytosis and Heinz bodies in pre-transfusion complete blood picture in all studied cases. G6PD assay show marked decrease in enzyme level at time of presentation in all cases with the commonest G6PD enzyme level of 3-4 U/gm Hb (592 patients; 59.2%). Conclusion and Recommendations: G6PD deficiency anemia presented mainly with pallor, dark red urine and jaundice after exposure to certain diets, drugs and diseases and therefore patients with G6PD deficiency should avoid exposure to these precipitating factors of hemolysis. We can also recommend large neonatal screening programs to detect cases of G6PD deficiency before the occurrence of acute hemolysis and molecular studies to detect G6PD enzyme variant in Egypt.
Keywords: G6PD deficiency anemia